2005
DOI: 10.1002/macp.200500164
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Relaxation of Side‐Chain Liquid Crystalline Ionomers Containing Alkaline Metal Ions

Abstract: Summary: Two sets of side‐chain, liquid‐crystalline ionomers based on copolymers of butyl acrylate and 4‐{[6‐(acryloyloxy)hexyl]oxy}benzoic acid containing 2.5–20 mol‐% of lithium or rubidium ions were studied. As the content of ions of alkali metals increases, segmental mobility markedly decreases. As compared with rubidium‐containing ionomers, ionomers containing lithium ions are characterized by a far more efficient decrease in their dielectric relaxation times because ionic radius of lithium ions is lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
4
0
1
Order By: Relevance
“…As a result, the relaxation process 2 in CB5PR is attributable to the rotational motion of α-CD around the PEG axis. This relaxation mode can referred to as δ-relaxation, which is often observed in side-group liquid-crystalline polymers [28][29][30]. These experimental results of the dielectric relaxation suggest the presence of high-mobility mesogenic side-chains in this novel liquid-crystalline polymer based on polyrotaxane.…”
Section: Processmentioning
confidence: 52%
“…As a result, the relaxation process 2 in CB5PR is attributable to the rotational motion of α-CD around the PEG axis. This relaxation mode can referred to as δ-relaxation, which is often observed in side-group liquid-crystalline polymers [28][29][30]. These experimental results of the dielectric relaxation suggest the presence of high-mobility mesogenic side-chains in this novel liquid-crystalline polymer based on polyrotaxane.…”
Section: Processmentioning
confidence: 52%
“…Unlike r(t/a T ), the function e(t/a T ) does not appear to be single-valued over the entire range of t and temperature, even though that behavior may be a reasonable approximation for some regimes of response, as discussed below. Comparison with similar deviations seen with certain polymers with liquid-crystalline side chains will be discussed below [8].…”
Section: Introductionmentioning
confidence: 76%
“…Since analysis of data on the dependence of the intrinsic viscosity on molecular weight indicates that b a=M L is about the same for PnBuA and poly(ethyl acrylate), PEA [15], the published data on h as a function of DP w and DP c for PEA provide a convenient comparison with the data here on PnBuA, and will be introduced in the following. The simple expression gzl þ h ð3p À 2Þ=p 2 i ð1 À lÞ 7=3 (8) for g ¼ ðR 2 G Þ br =ðR 2 G Þ lin provides a close representation of g for star and comb-shaped branched chains, with p the number of branches and l the fraction of chain units in the backbone (e.g., tending to unity and zero as the chain adopts linear or star-shaped structures, respectively) [16]. It has been suggested that an equivalent expression with g replaced by the ratio b g ¼ ðR 2 G Þ long =ðR 2 G Þ lin ¼ M long =M be used to estimate h for randomly-branched chains, where ðR 2 G Þ long and M long are the mean-square radius of gyration and the molecular weight, respectively, of the longest linear sequence that exists in the branched structure [17].…”
Section: Viscoelastic Propertiesmentioning
confidence: 99%
“…This technology was developed into a fully automated measuring system in collaboration with the company Novocontrol. Kremer recently discussed the dielectric relaxation of side‐chain liquid‐crystalline ionomers that contain alkaline metal ions 3. Besides dielectric spectroscopy, his research group also employs NMR and (time‐resolved) IR spectroscopy as well as optical and scanning probe methods to investigate the structure and dynamics of supramolecular systems, for example, near glass transitions.…”
Section: Awarded…︁mentioning
confidence: 99%